Association of Menstrual Cycle Pattern with Perceived Stress Score among Student and Staff Nurses - Zohra Parveen, Bushra Parveen, Sidra Hameed, Sarafeen Yousaf, Madiha Haroon (Pakistan Journal of Medical & Health Sciences, 2022)
Aims: To determine the menstrual cycle patterns among student and staff nurses and to compare levels of perceived stressed score and determine its association with menstrual cycle pattern. Study design: Cross-sectional study Place and duration of study: Shaikha Fatima Institute of Nursing and Health Sciences Lahore from 1st February to 1st July 2021. Methodology: One hundred and fifty participants aged 18 years containing information related to menstrual cycle patterns and problems related to menstrual cycle and perceived stress scale questionnaire. Results: Most common premenstrual symptom was generalized pain was found in 20 (26.0%) of student nurses and 12 (16.0%) of staff nurses. Mood swing was found to be highest among the negative effects of menstrual cycle reported by 39 (52.0%) of students and 35 (46.7%) staff nurses. No statistically significant difference was found between perceive stress scores of student and staff nurses.27.3% of participants having high level of perceived stress score were also experiencing irregular cycle. It was observed that irregular patterns of menstrual cycle was highly associated with high perceived stress score (p < 0.0001). Conclusion: Irregular menstrual cycle among student and staff nurses were strongly related with perceived stress score. Therefore, it was suggested that student and staff nurses should be counselled by psychologist as well as by a gynecologist in order to prevent future complications.